Waterproof coating adhesive and preparation method thereof

By combining modified neoprene with triazine A resin and adding components such as core-shell structure stabilization particles to form a crosslinking network system, the shortcomings of traditional neoprene adhesives in waterproofness and temperature adaptability are solved, and high bond strength and durability are achieved.

CN119505767APending Publication Date: 2025-02-25GUANGDONG SHUNDE JINMEI INTELLIGENT IDENTIFICATION TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411848378.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional neoprene adhesives have shortcomings in waterproofness and temperature adaptability, which leads to unstable bonding in environments with large temperature differences or alternating hot and cold, limiting their application range.

Method used

By combining modified neoprene with triazine A resin, and adding core-shell structure stabilizing particles, plasticizers and initiators, a crosslinking network system is formed to improve the waterproof performance and temperature adaptability of the colloidal material.

Benefits of technology

The high bond strength retention rate of colloidal materials in water immersion and high and low temperature cycle environments is achieved, which significantly improves its waterproof performance and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189891060000161
    Figure BDA0005189891060000161
Patent Text Reader

Abstract

The invention provides a waterproof coating adhesive and a preparation method thereof, and belongs to the technical field of adhesives, the waterproof coating adhesive comprises the following components: modified chloroprene rubber, triazine A resin, a solvent, core-shell structure stable particles, a plasticizer and an initiator. The waterproof coating adhesive prepared by the invention is high in bonding strength, good in waterproof performance, relatively high in temperature adaptability, relatively high in bonding strength retention rate when being soaked in water and in a cold and hot alternate environment, capable of adapting to changes of different environments and excellent in durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a waterproof coating adhesive and a preparation method thereof. Background Art

[0002] Waterproof coating glue is a material used for waterproofing to prevent water from penetrating certain parts. Neoprene, as a traditional bulk adhesive, is commonly known as all-purpose glue. It has high crystallinity and the resulting initial bonding strength. However, due to its molecular structure, it is difficult for chloroprene rubber to completely solve the waterproof and temperature adaptability problems by itself, which affects the durability of the product.

[0003] By compounding triazine A resin with chloroprene rubber, the moisture absorption of the colloidal material can be greatly reduced and the waterproof performance of the material can be effectively improved. However, the temperature adaptability problem is difficult to improve effectively. When used in an environment with large temperature differences or alternating hot and cold environments, the colloidal material is prone to bonding cracking and peeling, which limits the application scope of the waterproof coating adhesive. Summary of the invention

[0004] In order to solve the problems existing in the background technology, the present invention provides a waterproof coating adhesive and a preparation method thereof.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] A waterproof coating adhesive consists of the following components by weight: 70-80 parts of modified chloroprene rubber, 20-30 parts of triazine A resin, 8-12 parts of solvent, 4-6 parts of core-shell structure stabilizing particles, 2-4 parts of plasticizer and 0.5-1 part of initiator; the modified chloroprene rubber is acrylate grafted chloroprene rubber.

[0007] Furthermore, the solvent is one of toluene, xylene, butanone and acetone, or a mixture of at least two of them.

[0008] Furthermore, the plasticizer is one of trioctyl phosphate, citrate and dioctyl phthalate, or a mixture of at least two of them.

[0009] Furthermore, the initiator is a mixture of benzoyl peroxide and zinc isooctanoate / zinc isooctanoate in a mass ratio of 9:2-4.

[0010] Furthermore, the initiator is a mixture of benzoyl peroxide and zinc isooctanoate in a mass ratio of 3:1.

[0011] By compounding triazine A resin with modified chloroprene rubber, the low hygroscopicity of triazine A resin can effectively improve the waterproof performance of the colloid material, so that the colloid material has a higher shear strength retention rate after being immersed in water.

[0012] Further, the preparation of the modified chloroprene rubber comprises the following steps:

[0013] In parts by weight, 100 parts of chloroprene rubber and 20-40 parts of toluene are added to a reactor, mixed evenly, the reactor is heated to 60-80°C, stirred for 0.5-1h, 30-50 parts of acrylic resin monomer are added thereto, 0.4-0.6 parts of benzoyl peroxide are added, stirred for 1-2h, the temperature of the reactor is cooled to 45-55°C, 1-2 parts of hydroquinone are added, stirred for 5-10min, and modified chloroprene rubber is obtained.

[0014] Furthermore, the acrylic resin monomer is a mixture of methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:1.

[0015] By grafting chloroprene rubber with acrylate, on the one hand, the compatibility between the components can be improved and the initial bonding performance of the colloid can be enhanced; on the other hand, it helps to stabilize the uniform distribution of particles in the colloid material. Since acrylate has more polar groups, it can provide a basis for the formation of stable network nodes for stable particles, thereby giving the colloid a certain deformation ability under the condition of the presence of stable particles, and improving its bonding strength in high and low temperature cycle environments.

[0016] Furthermore, the preparation method of the core-shell structure stable particles is as follows:

[0017] 1. Disperse boron nitride particles with a particle size range of 10-30 microns in anhydrous ethanol, wherein the mass ratio of boron nitride particles to anhydrous ethanol is 1:10-20, add silane coupling agent KH550 to the dispersion, the amount of silane coupling agent added is 2-4% of the mass of boron nitride, stir for 20-40 minutes, filter, and obtain pretreated boron nitride particles;

[0018] 2. The pretreated boron nitride particles in step A1 are mixed with oleic acid and then ball-milled, the mass ratio of the pretreated boron nitride particles to the oleic acid being 1:3, the ball-milling time being 0.5-1.5 h, and filtered to obtain modified boron nitride particles;

[0019] 3. Add fine asphalt and graphite to the modified boron nitride particles of step A2, and then pour them into a high-speed mixer, stir for 2-4 hours, mix evenly, and obtain a mixture, wherein the mass ratio of modified boron nitride particles, asphalt and graphite is 5:1:1;

[0020] 4. The mixture was transferred to a tube furnace, and under nitrogen protection, the temperature was raised to 1000-1200°C at 3-5°C / min, and kept at this temperature for 4-6 hours, and naturally cooled to room temperature, and passed through a sieve to obtain stable particles with a core-shell structure.

[0021] Furthermore, the sieve is a 200-mesh sieve.

[0022] By modifying boron nitride and coating it with porous carbon sources, the boron nitride surface has more active sites, which can establish connections with polar groups in acrylates, thereby achieving effective combination of colloidal materials and inorganic materials. At the same time, the colloidal material is filled in the porous structure of the core-shell structured stable particles, which can provide them with the deformation space required for temperature changes. Ultimately, the colloidal material has a higher adaptability to temperature changes and improves its bonding strength retention rate in high and low temperature cycle environments.

[0023] A method for preparing a waterproof coating adhesive comprises the following steps:

[0024] S1. According to the mass percentage, weigh the raw materials, add triazine A resin, one-third of the initiator and one-third of the solvent into the reactor, heat to 60-70 ° C under nitrogen as the protective gas, stir for 2-3h, and obtain colloid A;

[0025] S2. Add the core-shell structure stable particles to the modified chloroprene rubber and stir for 0.5-1h to obtain colloid B;

[0026] S3. Add colloid B to colloid A in step S1, add the remaining initiator and solvent, stir for 1-2 hours, add plasticizer, stir for 10-20 minutes, and obtain the waterproof coating glue.

[0027] This application has the following beneficial effects:

[0028] 1. The present invention provides a waterproof coating adhesive and a preparation method thereof. The prepared waterproof coating adhesive has high bonding strength and good waterproof performance. At the same time, it has strong temperature adaptability, has a high bonding strength retention rate in water immersion and alternating hot and cold environments, can adapt to changes in different environments, and has excellent durability.

[0029] 2. Through the effective combination of triazine A resin, core-shell structure stabilized particles and modified chloroprene rubber, a cross-linked network system with core-shell structure stabilized particles as nodes is formed. At the same time, the active interface formed by the porous carbon source coated with boron nitride enables the core-shell structure stabilized particles to be effectively connected with the polar groups of acrylate, ultimately achieving a high degree of adaptability of the colloidal material to harsh environments, and making the colloidal material have higher waterproof performance and temperature stability. DETAILED DESCRIPTION

[0030] The present application is further described in detail below with reference to the embodiments.

[0031] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0032] Example 1

[0033] A waterproof coating adhesive comprises the following components based on weight of raw materials: 75 parts of modified chloroprene rubber, 25 parts of triazine A resin, 10 parts of solvent, 5 parts of core-shell structure stable particles, 3 parts of plasticizer and 0.8 parts of initiator.

[0034] Chloroprene rubber (SN244X) was purchased from Shanna Synthetic Rubber Co., Ltd.

[0035] Triazine A resin (C07PS) was purchased from Yangzhou Tianqi New Materials Co., Ltd.

[0036] The solvent is toluene.

[0037] The plasticizer is trioctyl phosphate.

[0038] The initiator is a mixture of benzoyl peroxide and zinc isooctanoate in a mass ratio of 3:1.

[0039] The preparation of the modified chloroprene rubber comprises the following steps:

[0040] In parts by weight, 100 parts of chloroprene rubber and 30 parts of toluene were added to a reactor and mixed evenly. The reactor was heated to 70°C and stirred for 0.5 h. 40 parts of a mixture of methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:1 were added thereto. 0.5 parts of benzoyl peroxide were added and stirred for 1.5 h. The temperature of the reactor was cooled to 50°C, 1.5 parts of hydroquinone were added and stirred for 5 min to obtain modified chloroprene rubber.

[0041] The preparation method of the core-shell structure stable particles is as follows:

[0042] 1. Disperse boron nitride particles with a particle size of 15 microns in anhydrous ethanol, wherein the mass ratio of boron nitride particles to anhydrous ethanol is 1:15, add silane coupling agent KH550 to the dispersion, the amount of silane coupling agent added is 3% of the mass of boron nitride, stir for 30 minutes, filter, and obtain pretreated boron nitride particles;

[0043] 2. The pretreated boron nitride particles in step A1 are mixed with oleic acid and then ball-milled. The mass ratio of the pretreated boron nitride particles to the oleic acid is 1:3. The ball-milling time is 1 hour. The mixture is filtered to obtain modified boron nitride particles.

[0044] 3. Add fine asphalt and graphite to the modified boron nitride particles of step A2, and then pour them into a high-speed mixer and stir for 3 hours to mix evenly to obtain a mixture, wherein the mass ratio of the modified boron nitride particles, asphalt and graphite is 5:1:1;

[0045] 4. The mixture was transferred to a tube furnace, and under nitrogen protection, the temperature was raised to 1100°C at 4°C / min, kept warm for 5 hours, naturally cooled to room temperature, and passed through a 200-mesh sieve to obtain stable particles with a core-shell structure.

[0046] A method for preparing a waterproof coating adhesive comprises the following steps:

[0047] S1. According to the weight percentage, weigh the raw materials, add the triazine A resin, one-third of the initiator and one-third of the solvent into the reactor, heat to 65 ° C under nitrogen as the protective gas, stir for 2.5h, and obtain colloid A;

[0048] S2. Add the core-shell structure stable particles to the modified chloroprene rubber and stir for 0.5 h to obtain colloid B;

[0049] S3. Add colloid B to colloid A in step S1, add the remaining initiator and solvent, stir for 2 hours, add plasticizer, stir for 15 minutes, and obtain the waterproof coating glue.

[0050] Example 2

[0051] A waterproof coating adhesive is composed of the following components by weight: 80 parts of modified chloroprene rubber, 20 parts of triazine A resin, 10 parts of solvent, 6 parts of core-shell structure stabilizing particles, 2 parts of plasticizer and 1 part of initiator; the modified chloroprene rubber is acrylate grafted chloroprene rubber.

[0052] The solvent is xylene.

[0053] The plasticizer is citrate.

[0054] The initiator is a mixture of benzoyl peroxide and zinc isooctanoate in a mass ratio of 3:1.

[0055] The preparation of the modified chloroprene rubber comprises the following steps:

[0056] In parts by weight, 100 parts of chloroprene rubber and 40 parts of toluene were added to a reactor and mixed evenly. The reactor was heated to 80°C and stirred for 1 hour. 50 parts of a mixture of methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:1 were added thereto. 0.6 parts of benzoyl peroxide were added and stirred for 2 hours. The temperature of the reactor was cooled to 55°C, 2 parts of hydroquinone were added and stirred for 10 minutes to obtain modified chloroprene rubber.

[0057] The preparation method of the core-shell structure stable particles is as follows:

[0058] 1. Disperse boron nitride particles with a particle size of 30 microns in anhydrous ethanol, wherein the mass ratio of boron nitride particles to anhydrous ethanol is 1:20, add silane coupling agent KH550 to the dispersion, the amount of silane coupling agent added is 4% of the mass of boron nitride, stir for 40 minutes, filter, and obtain pretreated boron nitride particles;

[0059] 2. The pretreated boron nitride particles in step A1 were mixed with oleic acid and then ball-milled. The mass ratio of the pretreated boron nitride particles to the oleic acid was 1:3. The ball-milling time was 1.5 h. The mixture was filtered to obtain modified boron nitride particles.

[0060] 3. Add fine asphalt and graphite to the modified boron nitride particles of step A2, and then pour them into a high-speed mixer and stir for 4 hours to mix them evenly to obtain a mixture, wherein the mass ratio of the modified boron nitride particles, asphalt and graphite is 5:1:1;

[0061] 4. The mixture was transferred to a tube furnace, and under nitrogen protection, the temperature was raised to 1200°C at 5°C / min, kept warm for 6 hours, cooled naturally to room temperature, and passed through a 200-mesh sieve to obtain stable particles with a core-shell structure.

[0062] A method for preparing a waterproof coating adhesive comprises the following steps:

[0063] S1. According to the mass percentage, weigh the raw materials, add triazine A resin, one-third of the initiator and one-third of the solvent into the reactor, heat to 70 ° C under nitrogen as the protective gas, stir for 2h, and obtain colloid A;

[0064] S2. Add the core-shell structure stable particles to the modified chloroprene rubber and stir for 1 h to obtain colloid B;

[0065] S3. Add colloid B to colloid A in step S1, add the remaining initiator and solvent, stir for 1 hour, add plasticizer, stir for 20 minutes, and obtain the waterproof coating glue.

[0066] Example 3

[0067] A waterproof coating adhesive is composed of the following components by weight: 72 parts of modified chloroprene rubber, 28 parts of triazine A resin, 12 parts of solvent, 4 parts of core-shell structure stabilizing particles, 2 parts of plasticizer and 0.5 parts of initiator; the modified chloroprene rubber is acrylate grafted chloroprene rubber.

[0068] The solvent is a mixture of toluene and xylene in a mass ratio of 1:1.

[0069] The plasticizer is trioctyl phosphate.

[0070] The initiator is a mixture of benzoyl peroxide and zinc isooctanoate in a mass ratio of 3:1.

[0071] The preparation of the modified chloroprene rubber comprises the following steps:

[0072] In parts by weight, 100 parts of chloroprene rubber and 35 parts of toluene were added to a reactor and mixed evenly. The reactor was heated to 80°C and stirred for 0.51h. 30 parts of a mixture of methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:1 were added thereto. 0.4 parts of benzoyl peroxide were added and stirred for 1h. The temperature of the reactor was cooled to 55°C, 1 part of hydroquinone was added and stirred for 5min to obtain modified chloroprene rubber.

[0073] The preparation method of the core-shell structure stable particles is as follows:

[0074] 1. Disperse boron nitride particles with a particle size of 30 microns in anhydrous ethanol, wherein the mass ratio of boron nitride particles to anhydrous ethanol is 1:10, add silane coupling agent KH550 to the dispersion, the amount of silane coupling agent added is 2% of the mass of boron nitride, stir for 30 minutes, filter, and obtain pretreated boron nitride particles;

[0075] 2. The pretreated boron nitride particles in step A1 are mixed with oleic acid and then ball-milled. The mass ratio of the pretreated boron nitride particles to the oleic acid is 1:3. The ball-milling time is 1 hour. The mixture is filtered to obtain modified boron nitride particles.

[0076] 3. Add fine asphalt and graphite to the modified boron nitride particles of step A2, and then pour them into a high-speed mixer and stir for 2 hours to mix evenly to obtain a mixture, wherein the mass ratio of the modified boron nitride particles, asphalt and graphite is 5:1:1;

[0077] 4. The mixture was transferred to a tubular furnace, and under nitrogen protection, the temperature was raised to 1200°C at 3°C / min, kept at this temperature for 4 hours, cooled naturally to room temperature, and passed through a 200-mesh sieve to obtain stable particles with a core-shell structure.

[0078] A method for preparing a waterproof coating adhesive comprises the following steps:

[0079] S1. According to the mass parts, weigh the raw materials, add the triazine A resin, one-third of the initiator and one-third of the solvent into the reactor, heat to 60 ° C under the condition of nitrogen as the protective gas, stir for 3h, and obtain colloid A;

[0080] S2. Add the core-shell structure stable particles to the modified chloroprene rubber and stir for 0.5 h to obtain colloid B;

[0081] S3. Add colloid B to colloid A in step S1, add the remaining initiator and solvent, stir for 2 hours, add plasticizer, stir for 10 minutes, and obtain the waterproof coating glue.

[0082] Example 4

[0083] A waterproof coating adhesive is composed of the following components by weight: 70 parts of modified chloroprene rubber, 30 parts of triazine A resin, 10 parts of solvent, 4 parts of core-shell structure stabilizing particles, 3 parts of plasticizer and 1 part of initiator; the modified chloroprene rubber is acrylate grafted chloroprene rubber.

[0084] The solvent is butanone.

[0085] The plasticizer is dioctyl phthalate.

[0086] The initiator is a mixture of benzoyl peroxide and zinc isooctanoate in a mass ratio of 3:1.

[0087] The preparation of the modified chloroprene rubber comprises the following steps:

[0088] In parts by weight, 100 parts of chloroprene rubber and 20 parts of toluene were added to a reactor and mixed evenly. The reactor was heated to 60°C and stirred for 1 hour. 30 parts of a mixture of methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:1 were added thereto. 0.4 parts of benzoyl peroxide were added and stirred for 2 hours. The temperature of the reactor was cooled to 45°C, 1 part of hydroquinone was added and stirred for 10 minutes to obtain modified chloroprene rubber.

[0089] The preparation method of the core-shell structure stable particles is as follows:

[0090] 1. Disperse boron nitride particles with a particle size of 10 microns in anhydrous ethanol, wherein the mass ratio of boron nitride particles to anhydrous ethanol is 1:20, add silane coupling agent KH550 to the dispersion, the amount of silane coupling agent added is 2% of the mass of boron nitride, stir for 40 minutes, filter, and obtain pretreated boron nitride particles;

[0091] 2. The pretreated boron nitride particles in step A1 are mixed with oleic acid and then ball-milled, the mass ratio of the pretreated boron nitride particles to oleic acid is 1:3, the ball-milling time is 0.5 h, and filtered to obtain modified boron nitride particles;

[0092] 3. Add fine asphalt and graphite to the modified boron nitride particles of step A2, and then pour them into a high-speed mixer and stir for 2 hours to mix evenly to obtain a mixture, wherein the mass ratio of the modified boron nitride particles, asphalt and graphite is 5:1:1;

[0093] 4. The mixture was transferred to a tube furnace, and under nitrogen protection, the temperature was raised to 1000°C at 3°C / min, kept at this temperature for 4 hours, cooled naturally to room temperature, and passed through a 200-mesh sieve to obtain stable particles with a core-shell structure.

[0094] A method for preparing a waterproof coating adhesive comprises the following steps:

[0095] S1. According to the mass parts, weigh the raw materials, add the triazine A resin, one-third of the initiator and one-third of the solvent into the reactor, heat to 60 ° C under the condition of nitrogen as the protective gas, stir for 3h, and obtain colloid A;

[0096] S2. Add the core-shell structure stable particles to the modified chloroprene rubber and stir for 0.5 h to obtain colloid B;

[0097] S3. Add colloid B to colloid A in step S1, add the remaining initiator and solvent, stir for 2 hours, add plasticizer, stir for 10 minutes, and obtain the waterproof coating glue.

[0098] Example 5

[0099] A waterproof coating adhesive is composed of the following components by weight: 78 parts of modified chloroprene rubber, 22 parts of triazine A resin, 11 parts of solvent, 5 parts of core-shell structure stabilizing particles, 3 parts of plasticizer and 0.8 parts of initiator; the modified chloroprene rubber is acrylate grafted chloroprene rubber.

[0100] The solvent is acetone.

[0101] The plasticizer is a mixture of trioctyl phosphate and dioctyl phthalate in a mass ratio of 1:1.

[0102] The initiator is a mixture of benzoyl peroxide and zinc isooctanoate in a mass ratio of 3:1.

[0103] The preparation of the modified chloroprene rubber comprises the following steps:

[0104] In parts by weight, 100 parts of chloroprene rubber and 20 parts of toluene were added to a reactor and mixed evenly. The reactor was heated to 60°C and stirred for 1 hour. 30 parts of a mixture of methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:1 were added thereto. 0.4 parts of benzoyl peroxide were added and stirred for 1 minute. The temperature of the reactor was cooled to 55°C, 1 part of hydroquinone was added and stirred for 5 minutes to obtain modified chloroprene rubber.

[0105] The preparation method of the core-shell structure stable particles is as follows:

[0106] 1. Disperse boron nitride particles with a particle size of 15 microns in anhydrous ethanol, wherein the mass ratio of boron nitride particles to anhydrous ethanol is 1:12, add silane coupling agent KH550 to the dispersion, the amount of silane coupling agent added is 2% of the mass of boron nitride, stir for 20 minutes, filter, and obtain pretreated boron nitride particles;

[0107] 2. The pretreated boron nitride particles in step A1 were mixed with oleic acid and then ball-milled. The mass ratio of the pretreated boron nitride particles to the oleic acid was 1:3. The ball-milling time was 1.5 h. The mixture was filtered to obtain modified boron nitride particles.

[0108] 3. Add fine asphalt and graphite to the modified boron nitride particles of step A2, and then pour them into a high-speed mixer and stir for 3 hours to mix evenly to obtain a mixture, wherein the mass ratio of the modified boron nitride particles, asphalt and graphite is 5:1:1;

[0109] 4. The mixture was transferred to a tube furnace, and under nitrogen protection, the temperature was raised to 1200°C at 4°C / min, kept warm for 6 hours, naturally cooled to room temperature, and passed through a 200-mesh sieve to obtain stable particles with a core-shell structure.

[0110] A method for preparing a waterproof coating adhesive comprises the following steps:

[0111] S1. According to the mass percentage, weigh the raw materials, add triazine A resin, one-third of the initiator and one-third of the solvent into the reactor, heat to 70 ° C under nitrogen as the protective gas, stir for 2h, and obtain colloid A;

[0112] S2. Add the core-shell structure stable particles to the modified chloroprene rubber and stir for 0.5 h to obtain colloid B;

[0113] S3. Add colloid B to colloid A in step S1, add the remaining initiator and solvent, stir for 1 hour, add plasticizer, stir for 20 minutes, and obtain the waterproof coating glue.

[0114] Comparative Example 1

[0115] The difference between this comparative example and Example 1 is that the chloroprene rubber in the raw material of the waterproof coating adhesive is not modified, and the triazine A resin is replaced by chloroprene rubber, and no core-shell structure stabilizing particles are added;

[0116] Specifically, a waterproof coating glue, the raw materials used are composed of the following components: 100 parts of chloroprene rubber, 10 parts of solvent, 3 parts of plasticizer and 0.8 parts of initiator.

[0117] Comparative Example 2

[0118] The difference between this comparative example and Example 1 is that: in the raw material of the waterproof coating glue, the triazine A resin is replaced by modified chloroprene rubber, and no core-shell structure stabilizing particles are added;

[0119] Specifically, a waterproof coating glue, the raw materials used are composed of the following components: 100 parts of modified chloroprene rubber, 10 parts of solvent, 3 parts of plasticizer and 0.8 parts of initiator.

[0120] Comparative Example 3

[0121] The difference between this comparative example and Example 1 is that: in the raw materials and preparation method of the waterproof coating adhesive, no triazine A resin is added, that is, the triazine A resin is replaced by modified chloroprene rubber;

[0122] Specifically, a waterproof coating glue, the raw materials used are composed of the following components: 100 parts of modified chloroprene rubber, 10 parts of solvent, 5 parts of core-shell structure stable particles, 3 parts of plasticizer and 0.8 parts of initiator.

[0123] Comparative Example 4

[0124] The difference between this comparative example and Example 1 is that in the raw materials and preparation method of the waterproof coating adhesive, the modified chloroprene rubber is replaced by chloroprene rubber;

[0125] Specifically, a waterproof coating glue, the raw materials used are composed of the following components: 75 parts of chloroprene rubber, 25 parts of triazine A resin, 10 parts of solvent, 5 parts of core-shell structure stable particles, 3 parts of plasticizer and 0.8 parts of initiator.

[0126] Comparative Example 5

[0127] The difference between this comparative example and Example 1 is that in the preparation of the core-shell structured stable particles, the stable particles are not coated with a porous carbon source;

[0128] Specifically, the preparation method of the core-shell structure stable particles is as follows:

[0129] 1. Disperse boron nitride particles with a particle size range of 10-30 microns in anhydrous ethanol, wherein the mass ratio of boron nitride particles to anhydrous ethanol is 1:15, add silane coupling agent KH550 to the dispersion, the amount of silane coupling agent added is 3% of the mass of boron nitride, stir for 30 minutes, filter, and obtain pretreated boron nitride particles;

[0130] 2. The pretreated boron nitride particles in step A1 are mixed with oleic acid and then ball-milled. The mass ratio of the pretreated boron nitride particles to the oleic acid is 1:3. The ball-milling time is 1 hour. The mixture is filtered to obtain modified boron nitride particles.

[0131] 3. Place the modified boron nitride particles in step A2 in a tubular furnace, and under nitrogen protection, heat to 1100°C at 4°C / min, keep warm for 5 hours, cool naturally to room temperature, and pass through a 200-mesh sieve to obtain stable particles with a core-shell structure.

[0132] Comparative Example 6

[0133] The difference between this comparative example and Example 1 is that the modified chloroprene rubber is replaced by chloroprene rubber, and in the preparation of the core-shell structured stable particles, the stable particles are not coated with a porous carbon source;

[0134] Performance Testing

[0135] Sample preparation: The surface of the aluminum plate substrate is coated by the coating method in GB / T 17657-2013, and the substrate coated with adhesive is bonded to obtain a sample, where the substrate size is 100×25mm 2 , the thickness of the adhesive layer is 0.2mm;

[0136] Shear strength test: According to GB / T 7124-2008 "Determination of tensile shear strength of adhesives", the shear strength of different materials was tested. The samples were placed in a standard environment of 23±2℃ / 50±5%RH for 1 day and then tested. The test speed was 5mm / min, where the shear strength retention rate = (shear strength before treatment - shear strength after treatment) / shear strength before treatment * 100%. The test results are shown in Table 1. The larger the shear strength value, the better the bonding performance of the waterproof adhesive.

[0137] Water immersion treatment: Place the sample in water at a temperature of 20±2℃ for 30 days. After immersion, wipe off the water attached to the surface of the sample, place the sample in a standard environment, let it stand for 24 hours, and test the shear strength. The higher the shear strength retention rate after immersion in water, the better the waterproof performance.

[0138] High and low temperature cycle treatment: Place the sample in a refrigerator at -20±2℃, freeze for 20 hours, take out the sample from the refrigerator, place it in a standard environment for 4 hours, put it in a drying oven at a temperature of 70±2℃, dry it for 20 hours, take out the sample from the drying oven, place it in a standard environment for 24 hours, and complete one cycle. After 10 cycles, place the sample in a standard environment, let it stand for 24 hours, and test the shear strength. The higher the shear strength retention rate after high and low temperature cycles, the better the high and low temperature cycle resistance and durability;

[0139] Table 1

[0140]

[0141] Results Analysis

[0142] It can be seen from the data in Table 1 that Examples 1-5 have high shear strength, and also have a relatively high shear strength retention rate after immersion in water and a relatively high shear strength retention rate after high and low temperature cycles, indicating that the waterproof coating adhesive provided by the present invention has high initial bonding strength, good waterproof performance, and strong temperature adaptability.

[0143] The data of Example 1, Comparative Examples 1-6 and Table 1 were analyzed, and the specific analysis results are as follows:

[0144] Compared with Example 1, in Comparative Example 3, no triazine A resin was added, and the shear strength retention rate after immersion in water was significantly reduced, indicating that the addition of triazine A resin can significantly improve the waterproof performance of the material.

[0145] Compared with Comparative Example 1, in Comparative Example 2, the chloroprene rubber was modified, and the shear strength was significantly improved, but the shear strength retention rate after high and low temperature cycles did not change significantly, indicating that the single modification of chloroprene rubber can improve the initial bonding strength of the colloid, but has no obvious effect on the high and low temperature cycle resistance of the colloid;

[0146] Compared with Comparative Example 6, in Comparative Example 4, the porous carbon source was coated on the stable particles, and the shear strength retention rate after high and low temperature cycles was significantly improved, indicating that the porous carbon source coating of the stable particles can improve the high and low temperature cycle resistance of the colloid;

[0147] Compared with Comparative Example 6, in Comparative Example 5, the chloroprene rubber was modified, and the shear strength retention rate after high and low temperature cycles was significantly improved, indicating that the modification of chloroprene rubber can improve the high and low temperature cycle resistance of the colloid;

[0148] Compared with Comparative Example 6, in Example 1, the stable particles are coated with a porous carbon source, and the chloroprene rubber is modified, and the shear strength retention rate after high and low temperature cycles is greatly improved;

[0149] Combining the data of Comparative Examples 1-2, Comparative Examples 4-6 and Example 1, it can be seen that the modification of chloroprene rubber can improve the high and low temperature cycle resistance of the colloid only when the stable particles are present. In addition, the modification of chloroprene rubber and the porous carbon source coating of the core-shell structure stable particles can both improve the high and low temperature cycle resistance of the colloid material. Moreover, the porous carbon source coating of the core-shell structure stable particles and the modified chloroprene rubber also have a certain synergistic effect. The combination of the two can significantly improve the high and low temperature cycle resistance of the colloid material.

[0150] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0151] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A waterproof coating adhesive, characterized in that: The waterproof coating adhesive is composed of the following components by weight: 70-80 parts of modified chloroprene rubber, 20-30 parts of triazine A resin, 8-12 parts of solvent, 4-6 parts of core-shell structure stabilizing particles, 2-4 parts of plasticizer and 0.5-1 part of initiator. The modified chloroprene rubber is acrylate grafted chloroprene rubber.

2. The waterproof coating glue according to claim 1, characterized in that: The preparation of the modified chloroprene rubber comprises the following steps: In parts by weight, 100 parts of chloroprene rubber and 20-40 parts of toluene are added to a reactor, mixed evenly, the reactor is heated to 60-80°C, stirred for 0.5-1h, 30-50 parts of acrylic resin monomer are added thereto, 0.4-0.6 parts of benzoyl peroxide are added, stirred for 1-2h, the temperature of the reactor is cooled to 45-55°C, 1-2 parts of hydroquinone are added, stirred for 5-10min, and modified chloroprene rubber is obtained.

3. The waterproof coating glue according to claim 2, characterized in that: The acrylic resin monomer is a mixture of methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:

1.

4. The waterproof coating glue according to claim 1, characterized in that: The preparation method of the core-shell structure stable particles is as follows: A1. Boron nitride particles with a particle size range of 10-30 microns are dispersed in anhydrous ethanol, wherein the mass ratio of boron nitride particles to anhydrous ethanol is 1:10-20, and a silane coupling agent KH550 is added to the dispersion, the amount of the silane coupling agent added is 2-4% of the mass of the boron nitride, stirred for 20-40 minutes, filtered, and pretreated boron nitride particles are obtained; A2. The pretreated boron nitride particles of step A1 are mixed with oleic acid and then ball-milled, the mass ratio of pretreated boron nitride particles to oleic acid is 1:3, the ball-milling time is 0.5-1.5h, and filtered to obtain modified boron nitride particles; A3. The modified boron nitride particles of step A2 are added with fine asphalt and graphite, and then poured into a high-speed mixer, stirred for 2-4 hours, and mixed evenly to obtain a mixture, wherein the mass ratio of the modified boron nitride particles, asphalt and graphite is 5:1:1; A4. The mixture was transferred to a tube furnace and heated to 1000-1200°C at 3-5°C / min under nitrogen protection, kept at this temperature for 4-6 hours, cooled naturally to room temperature, and passed through a sieve to obtain stable particles with a core-shell structure.

5. The waterproof coating glue according to claim 4, characterized in that: The sieve is a 200 mesh sieve.

6. The waterproof coating adhesive according to claim 1, wherein the solvent is one of toluene, xylene, butanone and acetone, or a mixture of at least two of them.

7. The waterproof coating glue according to claim 1, characterized in that: The plasticizer is one of trioctyl phosphate, citrate and dioctyl phthalate, or a mixture of at least two of them.

8. The waterproof coating adhesive according to claim 1, characterized in that: The initiator is a mixture of benzoyl peroxide and zinc isooctanoate in a mass ratio of 9:2-4.

9. The waterproof coating adhesive according to claim 1, characterized in that: The initiator is a mixture of benzoyl peroxide and zinc isooctanoate in a mass ratio of 3:

1.

10. A method for preparing a waterproof coating adhesive, characterized in that: Used to prepare the waterproof coating glue according to any one of claims 1 to 9, the preparation method comprises the following steps: S1. According to the mass percentage, weigh the raw materials, add triazine A resin, one-third of the initiator and one-third of the solvent into the reactor, heat to 60-70 ° C under nitrogen as the protective gas, stir for 2-3h, and obtain colloid A; S2. Add the core-shell structure stable particles to the modified chloroprene rubber and stir for 0.5-1h to obtain colloid B; S3. Add colloid B to colloid A in step S1, add the remaining initiator and solvent, stir for 1-2 hours, add plasticizer, stir for 10-20 minutes, and obtain the waterproof coating glue.